2014
DOI: 10.1071/fp13085
|View full text |Cite
|
Sign up to set email alerts
|

Negative short-term salt effects on the soybean–Bradyrhizobium japonicum interaction and partial reversion by calcium addition

Abstract: Abstract. The short-term (2 h) effects of salt stress (50 and 150 mM NaCl) on early events of soybean-Bradyrhizobium japonicum (rhizobia) interaction were analysed, determining the following parameters in root hair with or without calcium addition: deformation, apoplastic superoxide radical production (O 2 Á -), root hair death and sodium/potassium ion content. We also analysed whether this short-term salt stress influenced later formation of crown and noncrown nodules, determining the number and weight of nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…As mentioned above, the establishment of the symbiotic relationship between legumes and rhizobia depends on both local and systemic complex signaling pathways (Ferguson et al, 2018). In this regard, although the participation of local ROS signaling in roots after symbiont perception has been widely studied (Cárdenas et al, 2008; Muñoz et al, 2012, 2014a; Damiani et al, 2016), much less is known about the ROS systemic production during the legume–rhizobium interaction. We evaluated histochemically the systemic ROS (O 2 - and H 2 O 2 ) generation in leaves after 30, 60, 120 and 240 min of root inoculation with B. japonicum (Figure 1A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the establishment of the symbiotic relationship between legumes and rhizobia depends on both local and systemic complex signaling pathways (Ferguson et al, 2018). In this regard, although the participation of local ROS signaling in roots after symbiont perception has been widely studied (Cárdenas et al, 2008; Muñoz et al, 2012, 2014a; Damiani et al, 2016), much less is known about the ROS systemic production during the legume–rhizobium interaction. We evaluated histochemically the systemic ROS (O 2 - and H 2 O 2 ) generation in leaves after 30, 60, 120 and 240 min of root inoculation with B. japonicum (Figure 1A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Under moderate short-term salt stress (50 mM NaCl) treatment, B. japonicum could be sensed as a pathogen and its sensing may induce root hair cell death by a hypersensitive-like response and therefore may inhibit the nodulation process (Muñoz et al, 2012; Robert et al, 2014, 2018). Interestingly, the addition of calcium partially rescued the root hair death and inhibition of nodulation (Muñoz et al, 2014a). These results are in line with recent study that showed close similarities between symbiotic an immune pathway (Zipfel and Oldroyd, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the soybean-rhizobia symbiotic interaction process is also severely affected by stress conditions [19] , [20] . Our group has reported that salt stress, but not osmotic stress, negatively affect the early stages of the Glycine max L.- Bradyrhizobium japonicum interaction such as root hairs deformations and viability [23] , and how these short-term treatments affect nodule formation [24] . In this context, two root hairs death-inducing conditions were identified: sub lethal salt stress treatments combined with B. japonicum inoculation (inoculated 50 mM NaCl) and severe salt stress (150 mM NaCl).…”
Section: Introductionmentioning
confidence: 99%